2018
DOI: 10.5935/0004-2749.20180080
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of visual impairment, blindness and causes in the southwest region of São Paulo state, Brazil

Abstract: Visual impairment and blindness in the study population was low and mainly due to cataract and refractive errors. Initiatives should be addressed by health care services to further reduce avoidable blindness in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…17 This difference could be due to the dissimilar geographic location of studies and socioeconomic status of study sample. On the other hand,the present results are comparable with a study from Brazil 18 which reported that the leading causes were congenital cataract, toxoplasmosis, and congenital glaucoma.…”
Section: Discussionsupporting
confidence: 88%
“…17 This difference could be due to the dissimilar geographic location of studies and socioeconomic status of study sample. On the other hand,the present results are comparable with a study from Brazil 18 which reported that the leading causes were congenital cataract, toxoplasmosis, and congenital glaucoma.…”
Section: Discussionsupporting
confidence: 88%
“…As causas da deficiência visual e da cegueira variam em todo o mundo (7) sendo a catarata a principal causa mundial de cegueira (3,6,7,8). Em 2010 uma em cada três pessoas que ficaram cegas, foi decorrente a catarata (8) Erros de refração não corrigidos como a miopia, hipermetropia ou astigmatismo representam uma prevalência de 43% das causas de deficiência visual no mundo, segundo os relatórios da OMS de 2010 (6).…”
Section: Deficiência Visualunclassified